2009
DOI: 10.1890/08-2139.1
|View full text |Cite
|
Sign up to set email alerts
|

Lack of belowground mutualisms hinders Pinaceae invasions

Abstract: Abstract. Why particular invasions succeed and others fail is not well understood. The role of soil biota has been proposed as important. However, the role of mutualists has received much less attention than that of pathogens. Here we report that lack of adequate ectomycorrhizal fungi hinders invasion by exotic Pinaceae on Isla Victoria, Argentina, by reducing both the probability of establishment and growth of invading individuals. More than one hundred exotic tree species were introduced to this island ca. 8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
312
4
5

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 304 publications
(331 citation statements)
references
References 50 publications
10
312
4
5
Order By: Relevance
“…Although tree seedlings are able to survive short periods without ectomycorrhizal (ECM) fungal associates (Collier and Bidartondo, 2009), pine regeneration is often limited by lack of ECM fungal inoculum (Nunez et al, 2009). Thus, the initial recovery of forests after these severe mega-fires likely depends in part on whether appropriate ECM fungal spores have survived and are available to serve as partners for regenerating forest trees.…”
Section: Introductionmentioning
confidence: 99%
“…Although tree seedlings are able to survive short periods without ectomycorrhizal (ECM) fungal associates (Collier and Bidartondo, 2009), pine regeneration is often limited by lack of ECM fungal inoculum (Nunez et al, 2009). Thus, the initial recovery of forests after these severe mega-fires likely depends in part on whether appropriate ECM fungal spores have survived and are available to serve as partners for regenerating forest trees.…”
Section: Introductionmentioning
confidence: 99%
“…Mutualistic interactions can prevent or facilitate biological invasions (Richardson et al 2000, Nun˜ez et al 2009, Spence et al 2011) and determine the lag-phase between a species' introduction and subsequent invasion (Hallett 2006). Successful establishment and invasion of woody plants may be particularly sensitive to belowground symbiont availability, because many of these woody plant species depend on mutualistic microbes like mycorrhizal fungi and nitrogen-fixing bacteria (Nun˜ez and Dickie 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, recent research has revealed that both co-invasion of nonnative mutualist species and novel associations with native species determine invasion success (Pringle et al 2009, Dickie et al 2010, Nun˜ez and Dickie 2014, Wood et al 2015. For example, ectomycorrhizal pines appear to invade only when co-invading exotic or cosmopolitan fungi are available (Nun˜ez et al 2009, Dickie et al 2010, Hynson et al 2013, Hayward et al 2015, though introduced trees may form novel associations with native fungi as adults (Parlade´et al 1995, Jairus et al 2011, Trocha et al 2012, Bahram et al 2013. These studies also demonstrate that the importance of co-invasion in conferring invasion success is variable among studies or taxa, but the reasons for this are unresolved.…”
Section: Introductionmentioning
confidence: 99%
“…Propagules of plant species reached the bare land after glacier retreat, relying on the early arrival of fungi to absorb arid soil nutrients [54]. The relationship between the species migration and fungi has also been confirmed by modern ecological evidence [55]. Phenological changes caused by climate change may have had an important impact on insect pollination [56].…”
Section: The Role Of Environmental Factors In the Response Of Vegetatmentioning
confidence: 92%